(untitled) (World Bulletin of Public Health, 2023)
Dental caries is defined as a multi-factorial chronic infectious disease. The factors involve interactions between socioeconomic factors, behavioural factors, genetic factors, proteins related to antimicrobial activity, pH control, and bacterial colonization/adhesion